Baseline serum vitamin A and vitamin C levels and their association with disease severity in COVID-19 patients: Serum Vitamin A and C levels and COVID-19 severity - Yilmaz, Gulseren; Bulut, Huri; Ozden Omaygenc, Derya; Akca, Aysu; Can, Esra; Tuten, Nevin; Bestel, Aysegul; Erdem, Baki; Atmaca, Uygar Ozan; Kara, Yasin; Kaya, Ebru; Unsel, Murat; et al. (Acta Biomedica Atenei Parmensis, 2023)
Aim: We aimed to investigate the association between the serum concentrations of Vitamin A and Vitamin C and the severity of the COVID-19. Methods: Fifty-three consecutive PCR (+) COVID-19 patients admitted to a dedicated ward were enrolled in this study. Blood samples for serum Vitamin A and C measurements were drawn from all participants upon admission. All subjects underwent thoracic CT imaging prior to hospitalization. CT severity score (CT-SS) was then calculated for determining the extent of pulmonary involvement. A group of healthy volunteers, in whom COVID-19 was ruled out, were assigned to the control group (n=26). These groups were compared by demographic features and serum vitamin A and C levels. The relationship between serum concentrations of these vitamins and pre-defined outcome measures, CT-SS and length of hospitalization (LOH), was also assessed. Results: In COVID-19 patients, serum Vitamin A (ng/ml, 494±96 vs. 698±93; p